Abnormal Parietal Brain Function in ADHD: Replication and Extension of Previous EEG Beta Asymmetry Findings - Hale, T. Sigi; Kane, Andrea M.; Tung, Kelly L.; Kaminsky, Olivia; McGough, James J.; Hanada, Grant; Loo, Sandra K. (Frontiers in Psychiatry, 2014)
Background: Abundant work indicates ADHD abnormal posterior brain structure and function, including abnormal structural and functional asymmetries and reduced corpus callosum size. However, this literature has attracted considerably less research interest than fronto-striatal findings. Objective: To help address this imbalance, the current study replicates and extends our previous work showing abnormal parietal brain function in ADHD adults during the Conner’s continuous performance test (CPT). Method: Our previous study found that ADHD adults had increased rightward EEG beta (16-21 Hz) asymmetry in inferior parietal brain regions during the CPT (p=.00001), and that this metric exhibited a lack of normal correlation (i.e., observed in controls) with beta asymmetry at temporal-parietal regions. We re-tested these effects in a new ADHD sample, and with both new and old samples combined. We additionally examined: a) EEG asymmetry in multiple frequency bands, b) unilateral effects for all asymmetry findings, and c) the association between EEG asymmetry and a battery of cognitive tests. Results: We replicated our original findings, again demonstrating abnormal rightward inferior parietal beta asymmetry in adults with ADHD during the CPT, and again this metric exhibited abnormal reduced correlation to temporal-parietal beta asymmetry. Novel analyses also demonstrated a broader pattern of rightward beta and theta asymmetry across inferior, superior, and temporal-parietal brain regions, and showed that rightward parietal asymmetry in ADHD was atypically associated with multiple cognitive tests. Conclusion: Abnormal increased rightward parietal EEG beta asymmetry is an important feature of ADHD. We speculate that this phenotype may occur with any form of impaired capacity for top-down task-directed control over sensory encoding functions, and that it may reflect associated increases of attentional shifting and compensatory sustained/selective attention.